2009
DOI: 10.1007/s00454-009-9170-6
|View full text |Cite
|
Sign up to set email alerts
|

Markov Incremental Constructions

Abstract: A classic result asserts that many geometric structures can be constructed optimally by successively inserting their constituent parts in random order. These randomized incremental constructions (RICs) still work with imperfect randomness: the dynamic operations need only be "locally" random. Much attention has been given recently to inputs generated by Markov sources. These are particularly interesting to study in the framework of RICs, because Markov chains provide highly nonlocal randomness, which incapacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…If the walk is adversarial, we can achieve a similar result with near-linear storage. The former result is in the same spirit as previous work by the authors on randomized incremental construction (RIC) for Markov sources [3]. RIC is a fundamental algorithmic paradigm in computational geometry that uses randomness for the construction of certain geometric objects, and we showed that there is no significant loss of efficiency if the randomness comes from a Markov chain with sufficiently high conductance.…”
Section: Introductionsupporting
confidence: 79%
“…If the walk is adversarial, we can achieve a similar result with near-linear storage. The former result is in the same spirit as previous work by the authors on randomized incremental construction (RIC) for Markov sources [3]. RIC is a fundamental algorithmic paradigm in computational geometry that uses randomness for the construction of certain geometric objects, and we showed that there is no significant loss of efficiency if the randomness comes from a Markov chain with sufficiently high conductance.…”
Section: Introductionsupporting
confidence: 79%